2013
DOI: 10.3389/fpls.2013.00280
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the analysis of metal hyperaccumulation and hypertolerance in plants using proteomics

Abstract: Hyperaccumulator/hypertolerant plant species have evolved strategies allowing them to grow in metal-contaminated soils, where they accumulate high concentrations of heavy metals in their shoots without signs of toxicity. The mechanisms that allow enhanced metal uptake, root-to-shoot translocation and detoxification in these species are not fully understood. Complementary approaches such as transcriptomic-based DNA microarrays and proteomics have recently been used to gain insight into the molecular pathways ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…A recent study by Xin et al (2013) who investigated the role of roots in Cd accumulation in two water spinach cultivars using reciprocal grafting is an elegant example of the application of the technique. Current research has shown differential root-to-shoot regulation of photosynthetic proteins, sulphur and glutathione metabolism involved in signaling and secondary metabolism in Cd hyperaccumulation (Akhter et al 2014;DalCorso et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Xin et al (2013) who investigated the role of roots in Cd accumulation in two water spinach cultivars using reciprocal grafting is an elegant example of the application of the technique. Current research has shown differential root-to-shoot regulation of photosynthetic proteins, sulphur and glutathione metabolism involved in signaling and secondary metabolism in Cd hyperaccumulation (Akhter et al 2014;DalCorso et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Their degradation pathways or mechanisms of absorption were elucidated, and many genes for degradation have already been cloned. Moreover, many plants that can effectively absorb and accumulate metal ions have been discovered and those plants are known as hyperaccumulators [53,54]. For example, Rinorea nicolifera, which was recently discovered in Western Luzon, Philippines, could accumulate unusually high amounts (18,000 ppm) of nickel [55].…”
Section: Best Microorganisms and Plants To Remediate Pollution Of Soimentioning
confidence: 99%
“…It seems improbable that the hyperaccumulation trait, requiring, as it does, complex physiological adaptation (reviewed in DalCorso et al, 2013) would evolve in complementation of previously existing, costly defense mechanisms. However, given that certain innate defense mechanisms appear to have been dispensable when hyperaccumulators have had access to metals (e.g., Noret et al, 2007; Fones et al, 2013), it is possible that the costs imposed by the acquisition of adaptations for metal hyperaccumulation may have been outweighed by a reduction in the costs imposed by innate defense systems, coupled with the benefits of redeploying defense-related processes to increase metal tolerance.…”
Section: Interactions Between Metal Hyperaccumulation and Other Defensesmentioning
confidence: 99%